Thanksgiving Day - Rockwell, Anne F.; Rockwell, Lizzy ([New York] : HarperCollinsPublishers, 1999)
Mrs. Madoff$1 (Bs preschool class learns about Thanksgiving and puts on a play about the origins of the holiday.s
Keywords: Thanksgiving Day -- Fiction; Schools -- Fiction